The Aristotelian conception of habit and its contribution to human neuroscience - Bernacer, Javier; Murillo, Jose Ignacio (Frontiers in Human Neuroscience, 2014)
The notion of habit used in neuroscience is an inheritance from a particular theoretical origin, whose main source is William James. Thus, habits have been characterized as rigid, automatic, unconscious, and opposed to goal-directed actions. This analysis leaves unexplained several aspects of human behavior and cognition where habits are of great importance. We intend to demonstrate the utility that another philosophical conception of habit, the Aristotelian, may have for neuroscientific research. We first summarize the current notion of habit in neuroscience, its philosophical inspiration and the problems that arise from it, mostly centered on the sharp distinction between goal-directed actions and habitual behavior. We then introduce the Aristotelian view and we compare it with that of William James. For Aristotle, a habit is an acquired disposition to perform certain types of action. If this disposition involves an enhanced cognitive control of actions, it can be considered a “habit-as-learning”. The current view of habit in neuroscience, which lacks cognitive control and we term “habit-as-routine”, is also covered by the Aristotelian conception. He classifies habits into three categories: 1) theoretical, or the retention of learning understood as “knowing that x is so”; 2) behavioral, through which the agent achieves a rational control of emotion-permeated behavior (“knowing how to behave”); and 3) technical or learned skills (“knowing how to make or to do”). Finally, we propose new areas of research where this “novel” conception of habit could serve as a framework concept, from the cognitive enrichment of actions to the role of habits in pathological conditions. In all, this contribution may shed light on the understanding of habits as an important feature of human action. Habits, viewed as cognitively controlled behaviors that in turn improve cognitive control of behavior, are a crucial resource for enhancing human learning and behavioral plasticity.